Implementación del recurso digital Crea Infografías Interactivas con Genially, en la asignatura de Informática para el tercer año paralelo Cont en el Colegio de Bachillerato Beatriz Cueva de Ayora, de la ciudad de Loja, año lectivo 2022- 2023. - Macas Cuenca, Christian Andrés (2023)
In the context of the digital era and with the advance of information and communication technologies, the use of digital resources in education has gained increasing relevance. In the present study of the Curricular Integration Work, the technical, pedagogical, and methodological structure of the digital resource Crea Infografías Interactivas con Genially was described in detail, also, the digital resource is integrated into the microcurricular planning proposed by the teacher in unit two of the Computing subject, parallel Cont, adapting it to five planning based on the strategies of the TPACK methodology (Technical Pedagogical Knowledge of the Content). In this way, the digital resource is adjusted to the different didactic moments of the class, providing a more enriching experience for the students. The methodology used has been developed under a quantitative approach and a transversal research design with an exploratory-descriptive scope, with the participation of nineteen students and a teacher of General Unified High School in the Computing subject, parallel Cont of the Beatriz Cueva de Ayora High School, the data collection is carried out through the technique of observation, interview and survey. In this way, the inclusion of the digital resource Crea Interactive Infographics with Genially demonstrates to be beneficial in the teaching-learning process, as evidenced in the opinion of the students and the teacher, so after applying the digital resource in each of the classes reflects the acceptance and usefulness of the resource as an effective educational tool. Keywords: Digital resources, teaching-learning, interactive infographics, genially, classroom observation.